Rashid Johnson - a poem for deep thinkers / edited by Naomi Beckwith with Andrea Karnes ; with contributions by Nana Adusei Poku [and six others]. - Beckwith, Naomi; Karnes, Andrea; Johnson, Rashid, 1977- (Guggenheim New York, 2025)
From his early self-portraits to his site-specific installations, this volume underscores Rashid Johnson's fearless engagement with the central themes, questions and aesthetics of the contemporary era. It is a three-decade survey of Rashid Johnson's artistic career. It situates the artist within three interconnected spheres: as a scholar of art history; as a mediator of Black popular culture and its widespread commodification; and as an artist engaged with the globalization of contemporary art. The exhibition and accompanying catalogue feature nearly 90 artworks, including early photographs, Cosmic Slops, spray-painted text works, collage paintings, Broken Men mosaics, film projects, and key sculptures and installations that incorporate materials such as shea butter, black soap, plants, ceramic vessels and wax.